Knowledge and Attitude on Substance Abuse among Higher Secondary Schools Adolescents in Kathmandu District - Neupane, Sharmila; Darshandhari, Gayetri (Journal of Karnali Academy of Health Sciences, 2023)
Background: Substance abuse creates a great threat to the health, social and economic condition of individual, family, community and to the nation. In the past two decades’ abuse of substances is an important public health concern especially among adolescent which creates tremendous burden on society. So, researchers were interested to assess the knowledge and attitude of adolescents on substance abuse in higher secondary schools of Kathmandu district. Methods: A cross-sectional descriptive study design was used to assess the knowledge and attitude of adolescence on substance abuse. At first seven school and colleges was selected by the probability simple random sampling technique with 630 sample studying management and humanities. Data collection was done through selfadministered questionnaire. Results: More than half (59.2%) respondents have poor knowledge whereas only 8.6% have good level of knowledge on substance abuse, as only few have good level of knowledge on substance abuse. There is significant association between the level of knowledge with age group (p value 0.011), Sex (p value 0.001), Ethnicity (p value 0.001), type of family (p value 0.001) and father’s education (p value 0.027) mother’s education (p value 0.009), father occupation (p value 0.036), and relationship between parents (p value 0.01). Conclusion: More than half respondents have poor knowledge whereas only 8.6% have good level of knowledge on substance abuse. Though awareness campaigns exist in the country, but findings of this study suggest that still these activities need to be made more strengthen in order to make aware to the youth.